The influence of TiN and DLC deposition on the wear resistance of Nitinol – Ti6Al4V combination for the medical application. (2017) - Lukina, Elena; Kollerov, Mikhail; Meswania, Jay; Panin, Pavel; Khon, Alla; Blunn, Gordon
Abstract: The influence of the TiN and DLC coatings deposition on the wear resistance of Nitinol – Ti6Al4V friction pair for the potential application in fusionless sliding spinal implants for the scoliosis correction was studied in this work. Wear tests were carried out using pin-on-disc scheme in diluted calf serum. It was found that the deposition of TiN or DLC only on titanium component of the Nitinol – Ti6Al4V friction combination can significantly improve it's wear performance. Deposition of TiN or DLC coating on both components was found not to be effective due to delamination or wearing through of the coatings.